Identification of the antimicrobial substances produced by Solanum palinacanthum (Solanaceae) - Pereira, Aline C.; Oliveira, Denilson F.; Silva, Geraldo H. [UNESP]; Figueiredo, Henrique C.P.; Cavalheiro, Alberto José [UNESP]; Carvalho, Douglas A.; Souza, Luciana P.; Chalfoun, Sára M. (Academia Brasileira de Ciências, 2008)
Com vistas a descobrir antimicrobianos de origem natural para uso terapêutico ou para a preservação de alimentos, o extrato metanólico das partes aéreas de Solanum palinacanthum foi submetido a fracionamentos direcionados por testes para avaliar a atividade antibacteriana e antifúngica. em decorrência, o flavonóide rutina e o ácido 3,5-dicafeoilquínico foram isolados por cromatografia em coluna e por cromatografia líquida de alta eficiência, para serem identificados por espectrometria de massas e de ressonância magnética nuclear. As concentrações inibitórias mínimas (CIM) do derivado do ácido cafeico contra Aeromonas hydrophila, Bacillus subtilis, Staphylococcus aureus e o fungo Aspergillus ochraceus foram 250, 1000, 1000 e > 568µg/mL, respectivamente. Contra os mesmos organismos, os valores de CIM para a rutina foram 1000, > 1000, > 1000 e 35µg/mL, respectivamente. A rutina mostrou-se muito promissora para o controle de A. ochraceus, pois seu valor de CIM contra tal fungo foi bem próximo ao observado para o cloreto de benzalcônio, que é empregado como fungicida no Brasil.

To find out natural antimicrobial agents as alternative in therapeutics and to preserve food, the methanol extract of Solanum palinacanthum aerial parts was submitted to purification steps guided by antibacterial and antifungal assays. As a consequence, the flavonoid rutin and 3,5-dicaffeoylquinic acid were isolated by column chromatographyand high performance liquid chromatography, and identified by mass and nuclear magnetic resonance spectrometry. Minimal inhibitory concentrations (MIC) of the quinic acid derivative against Aeromonas hydrophila, Bacillus subtilis, Staphylococcus aureus and the fungus Aspergillus ochraceus were 250, 1000, 1000 and > 568µg/mL, respectively. Against the same microorganisms, MIC for rutin were 1000, > 1000, > 1000 and 35µg/mL, respectively. Rutinwas very promising for A. ochraceus control, since its MIC against such fungus was close to the one observed for benzalkonium chloride, which is used as a fungicide in Brazil.
Keywords: Solanum palinacanthum; ácido 3,5-dicafeoilquínico; rutina; antimicrobiano; Solanum palinacanthum; 3,5-dicaffeoylquinic acid; rutin; antimicrobial activity